2019
DOI: 10.1631/jzus.b1800530
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Effects of dietary glycerol monolaurate on productive performance, egg quality, serum biochemical indices, and intestinal morphology of laying hens

Abstract: Glycerol monolaurate (GML) has been widely used as an effective antibacterial emulsifier in the food industry. A total of 360 44-week-old Hy-Line brown laying hens were randomly distributed into four groups each with six replicates of 15 birds, and fed with corn-soybean-meal-based diets supplemented with 0, 0.15, 0.30, and 0.45 g/kg GML, respectively. Our results showed that 0.15, 0.30, and 0.45 g/kg GML treatments significantly decreased feed conversion ratios (FCRs) by 2.65%, 7.08%, and 3.54%, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…Liu et al [ 51 ] reported an increase in the jejunal villus length and VH: CD ratio in the duodenum and ileum by dietary GML. Zhao, et al [ 69 ] reported improved Intestinal morphology by GML supplementation indicated by increased VH and VH: CD ratio. Liu, et al [ 70 ] reported improved growth, muscle amino acids, and intestinal morphology in broilers by GML supplementation (300, 450, and 600 mg/kg) mostly by influencing the gut microbiota function and community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al [ 51 ] reported an increase in the jejunal villus length and VH: CD ratio in the duodenum and ileum by dietary GML. Zhao, et al [ 69 ] reported improved Intestinal morphology by GML supplementation indicated by increased VH and VH: CD ratio. Liu, et al [ 70 ] reported improved growth, muscle amino acids, and intestinal morphology in broilers by GML supplementation (300, 450, and 600 mg/kg) mostly by influencing the gut microbiota function and community.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, an increase in de novo fatty acid synthesis may cause a rise in the production of triglycerides [ 77 ]. Saeidi et al [ 43 ] reported that quail chicks fed on MCFA-supplemented diet showed decreased serum levels of TC, TG, LDL-C, and increased HDL-C. Zhao et al [ 69 ] reported an optimistic effect of GML supplementation on the lipid profile of laying hens indicated by reducing the the serum TG and TC levels and lowering the abdominal fat.…”
Section: Discussionmentioning
confidence: 99%
“…(2019) found that GML treatment may improve growth performance, reduce numbers of parasite oocysts and E. coli , and augment the production of globulins, while leaving meat quality unaltered. Moreover, Zhao et al. (2019) showed that dietary GML improved egg quality.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that GML can be used as a feed additive to improve animal growth performance and health ( Fortuoso et al., 2019 ; Zhao et al., 2019 ). Fortuoso et al.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have retracted this article (Zhao et al, 2019) due to significant overlap with a previously published Chinese language article (Liu et al, 2017), including overlap in Table 1, Table 2, Table 3, Table 6, Fig. 4, and part of the results (Sections 3.1, 3.2, 3.5, and 3.7).…”
mentioning
confidence: 99%